2017
DOI: 10.1002/adfm.201703174
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Self‐Healable and Dual Responsive Cellulose‐Based Hydrogels for Controlled Release and 3D Cell Culture

Abstract: To face the increasing demand of self-healing hydrogels with biocompatibility and high performances, a new class of cellulose-based self-healing hydrogels are constructed through dynamic covalent acylhydrazone linkages. The carboxyethyl cellulose-graft-dithiodipropionate dihydrazide and dibenzaldehyde-terminated poly(ethylene glycol) are synthesized, and then the hydrogels are formed from their mixed solutions under 4-amino-DL-phenylalanine (4a-Phe) catalysis. The chemical structure, as well as microscopic mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
217
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(221 citation statements)
references
References 48 publications
3
217
0
1
Order By: Relevance
“…Subsequently, the stabilities of hydrogels were further investigated by rheological measurements. As shown in Figure C,D, gelation was observed when the value of storage modulus (G′) exceeded that of loss modulus (G′′), and the gelation time decreased with the increase in gel concentration (Table S1, Supporting Information), which was consistent with the previous report . After gelation, the G′′ would gradually increase with time, indicating further formation of Schiff base linkages in the hydrogels.…”
Section: Resultssupporting
confidence: 89%
“…Subsequently, the stabilities of hydrogels were further investigated by rheological measurements. As shown in Figure C,D, gelation was observed when the value of storage modulus (G′) exceeded that of loss modulus (G′′), and the gelation time decreased with the increase in gel concentration (Table S1, Supporting Information), which was consistent with the previous report . After gelation, the G′′ would gradually increase with time, indicating further formation of Schiff base linkages in the hydrogels.…”
Section: Resultssupporting
confidence: 89%
“…It has been reported that hydrogels containing dynamic reversible crosslinks may promote the exchange of nutrients and metabolites between the cells and the external environment, and allow the cells to engage in complex cellular functions, which can represent an advantage in 3D cell culture compared with permanently crosslinked networks. 95,111,112 Therefore we believe that our proposed materials could constitute a robust remotely healable platform to encapsulate and release cells with applications in cell delivery technologies.…”
Section: Self-healing Propertiesmentioning
confidence: 99%
“…The disappearance of skeletal vibration of aromatic and presence of –NH– stretching band of EPL (3247 cm −1 ) suggested the formation of FEPL. In the FTIR spectrum of the FCE hydrogels, the disappearance of bands at 1687 cm −1 (aldehyde) and the new peak at 1662 cm −1 (CN), suggesting the Schiff base reaction between –CHO groups of F127‐Phe‐CHO and –NH 2 of FEPL …”
Section: Resultsmentioning
confidence: 99%
“…Fabrication and Characterizations of FCB Hydrogel : Dibenzaldehy determinated F127 (F127‐Phe‐CHO) and F127‐EPL (FEPL) copolymer was prepared in a similar method as described previously, as shown in Supporting Information . The FCB hydrogel was prepared through a facile mixing method.…”
Section: Methodsmentioning
confidence: 99%